HIV Infection and AIDS in Sub-Saharan Africa: Current Status, Challenges and Opportunities - Kharsany, Ayesha B.M. (Open AIDS J, 2016)
Global trends in HIV infection demonstrate an overall increase in HIV prevalence and substantial declines in AIDS related deaths largely attributable to the survival benefits of antiretroviral treatment. Sub-Saharan Africa carries a disproportionate burden of HIV, accounting for more than 70% of the global burden of infection. Success in HIV prevention in sub-Saharan Africa has the potential to impact on the global burden of HIV. Notwithstanding substantial progress in scaling up antiretroviral therapy (ART), sub-Saharan Africa accounted for 74% of the 1.5 million AIDS related deaths in 2013. Of the estimated 6000 new infections that occur globally each day, two out of three are in sub-Saharan Africa with young women continuing to bear a disproportionate burden. Adolescent girls and young women aged 15-24 years have up to eight fold higher rates of HIV infection compared to their male peers. There remains a gap in women initiated HIV prevention technologies especially for women who are unable to negotiate the current HIV prevention options of abstinence, behavior change, condoms and medical male circumcision or early treatment initiation in their relationships. The possibility of an AIDS free generation cannot be realized unless we are able to prevent HIV infection in young women. This review will focus on the epidemiology of HIV infection in sub-Saharan Africa, key drivers of the continued high incidence, mortality rates and priorities for altering current epidemic trajectory in the region. Strategies for optimizing the use of existing and increasingly limited resources are included.